Brand Image and Store Atmosphere as Predictors of Customer Satisfaction at One Sky Coffee & Lounge Payakumbuh - Mike Yulianti; Nidia Wulansari (Pt. Threeple Herphi Educate, 2026)
This study examines the effects of brand image and store atmosphere on customer satisfaction at One Sky Coffee & Lounge Payakumbuh, Indonesia. The research was motivated by preliminary customer concerns regarding product distinctiveness, access, and interior layout. A quantitative cross-sectional survey was conducted with 204 customers selected through purposive sampling from a population of 14,175 visitors. Data were collected using a five-point Likert-scale questionnaire and analyzed with multiple linear regression in SPSS 29. Brand image (70.4%), store atmosphere (67.4%), and customer satisfaction (73.8%) were categorized as good. The regression model was statistically significant, F(2, 201) = 9.063, p < 0.001. Brand image positively predicted customer satisfaction (B = 0.286, beta = 0.208, t = 3.076, p = 0.002), while store atmosphere also showed a positive effect (B = 0.181, beta = 0.192, t = 2.847, p = 0.005). However, the model explained only 8.3% of satisfaction variance (adjusted R-squared = 0.074), indicating that branding and atmosphere make statistically meaningful but limited contributions. Management should prioritize a distinctive signature-product identity and improve access, circulation, flooring, and interior comfort while also addressing food quality, service quality, price fairness, and waiting time.